2022
DOI: 10.23838/pfm.2021.00198
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies in central nervous system and neuromuscular autoimmune disorders: A narrative review

Abstract: The discovery of novel autoantibodies in neurological disorders contributes to a better understanding of its pathogenesis, improves the accuracy of diagnosis, and leads to new treatment strategies. Advances in techniques for the screening and detection of autoantibodies have enabled the discovery of new antibodies in the central nervous system (CNS) and neuromuscular diseases. Cell-based assays using live or fixed cells overexpressing target antigens are widely used for autoantibody-based diagnosis in clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 96 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…The clinical significance of MOG-Ab has been studied thoroughly with the discovery of reliable cell-based immunoassay for MOG-Ab using full-length human MOG protein and IgG1 antibody ( 9 ). The detection of MOG-Ab became an essential part of the differential diagnosis of CNS demyelinating diseases ( 5 , 10 ), and it has helped to expand our understanding of the clinical diversity of MOGAD; the clinical syndromes of MOGAD include single/recurrent or bilateral ON, TM, ADEM, brain or brainstem syndrome, and cortical encephalitis ( 2 , 5 , 11–13 ). In our study, patients with MOGAD also showed diverse clinical syndromes, and ON was the most common presenting clinical syndrome (38/55, 69.1%), which was in line with the results of previous studies ( 3 , 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of MOG-Ab has been studied thoroughly with the discovery of reliable cell-based immunoassay for MOG-Ab using full-length human MOG protein and IgG1 antibody ( 9 ). The detection of MOG-Ab became an essential part of the differential diagnosis of CNS demyelinating diseases ( 5 , 10 ), and it has helped to expand our understanding of the clinical diversity of MOGAD; the clinical syndromes of MOGAD include single/recurrent or bilateral ON, TM, ADEM, brain or brainstem syndrome, and cortical encephalitis ( 2 , 5 , 11–13 ). In our study, patients with MOGAD also showed diverse clinical syndromes, and ON was the most common presenting clinical syndrome (38/55, 69.1%), which was in line with the results of previous studies ( 3 , 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%